TATA KELOLA KEARSIPAN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KARANGANYAR - Asyifa Nida Silmia; Dyah Indrawati; Muhammad Umam (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
This study aims to determine: 1) implementation of archival management at BKPSDM Kabupaten Karanganyar, 2) obstacles in archival management at BKPSDM Kabupaten Karanganyar, 3) solutions to existing problems in archival management at BKPSDM Kabupaten Karanganyar. This research is a qualitative descriptive research with a case study approach. Research data obtained from informants, events, documents with purposive and snowball sampling. Data collection techniques by observation, interviews and documentation. The validity of the data was obtained by triangulation of techniques and sources. The data analysis technique used interactive model data analysis with the following stages: 1) data reduction, 2) data presentation, 3) data verification and conclusion drawing. The research procedure consists of the following stages: 1) preparation, 2) implementation and 3) the final stage. The results showed that: 1) implementation of archives management includes: (a) policies, (b) archiving development (c) archive management. 2) obstacles in archival management including: (a) no archiver available, (b) archive manager does not come from an archival science background, (c) insufficient archive facilities. 3) Solutions to overcome these obstacles include: (a) developing digital archives and creating web-based archiving systems, (b) collaborating with Dinas Kearsipan dan Perpustakaan Kabupaten Karanganyar to employees in the field of archive management.